Management from our Hindu Scriptures: A historical drive to our own India - Nishankbhai Vadia, Foraam; Badgujar, Hemangi A.; Patil, Sonal Umesh (Journal of Advanced Research in Service Management, 2023)
The research entails us the drive of management through the historic perspective. Whatever we have learnt in the corpus of management is seen as the western bequeath but it has been originated since the Ganges has initiated in the Vedic age, since nectar and poison has churned from the great ocean churn and the list goes on. All the above references could be from different cultural excavation but the mother of all Indian Ancient History.